TINGKAT PEMAHAMAN KOMPETENSI GURU PADA MAHASISWA PENDIDIKAN GEOGRAFI SEBAGAI CALON GURU GEOGRAFI - Novia Zalmita; Muhajirah Muhajirah; Abdul Wahab Abdi (JURNAL SERAMBI ILMU, 2020)
One that influences human resource indicators is education. The teacher is a profession as a job of academic specialization in a relatively long time in college. Understanding related to teacher competence is very important to have by a prospective teacher because it can affect the quality of performance as a professional teacher. The teacher's competence is known as pedagogic, professional, social and personality competencies. The issue in this study is how the competency of the teacher of the Department of Geography Education FKIP Unsyiah as a prospective teacher of geography? The purpose of this study was to determine the competence of teachers in the Department of Geography Education FKIP Unsyiah as prospective geography teachers. Quantitative description approach is used in this study to find answers to the issue. The population in this study were students of the Department of Geography Education FKIP Unsyiah class of 2015 and 2016 who had been declared to have passed the Micro Teaching and Magang Kependidikan 3 course totaling 50 people. Because the population is small and can be reached, the determination of the sample using total sampling techniques so that the sample in this study is the whole population. Data collection is done by distributing test questions to respondents. The data was analyzed using the descriptive statistics percentage formula. The results of the study indicate that the level of teacher competence of Geography Education Department students as prospective teachers is in the moderate category, namely as many as 22 respondents (44%). A total of 12 respondents (24%) were in the high category, 15 respondents (30%) were in the low category and 1 respondent (2%) were in the very low category.